The past, present, and future of opioid prescribing: Perioperative opioid use in gynecologic oncology patients after laparotomy at a single institution from 2012 to 2021 - Allison H. Kay; Alisha Othieno; John Boscardin; Lee-lynn Chen; Edwin A. Alvarez; Megan Swanson; Stefanie Ueda; Lee-may Chen; Jocelyn S. Chapman (Elsevier, 2023)
Objective: To describe the evolution of perioperative opioid management in gynecologic oncology patients after open surgeries and determine current opioid over-prescription rates. Methods: Part one of this two-part study was a retrospective chart review of adult patients who underwent laparotomy by a gynecologic oncologist from July 1, 2012 to June 30, 2021, comparing changes in clinical characteristics, pain management and discharge opioid prescription sizes between fiscal year 2012 (FY2012) and 2020 (FY2020). In part two, we prospectively surveyed patients after laparotomy in 2021 to determine opioid use after hospital discharge. Results: 1187 patients were included in the chart review. Demographic and surgical characteristics remained stable from FY2012 to FY2020 with differences notable for increased rates of interval cytoreductive surgeries for advanced ovarian cancer and decreased rates of full lymph node dissection. Median inpatient opioid use decreased by 62 % from FY2012 to FY2020. Median discharge opioid prescription size was 675 oral morphine equivalents (OME) per patient in FY2012 and decreased by 77.7 % to 150 OME in FY2020. Of 95 surveyed patients in 2021, median self-reported opioid use after discharge was 22.5 OME. Patients had an excess of opioids equivalent to 1331 doses of 5-milligram oxycodone tablets per 100 patients. Conclusion: Inpatient opioid use in our gynecologic oncology open surgical patients and post-discharge opioid prescription size significantly decreased over the last decade. Despite this progress, our current prescribing patterns continue to significantly overestimate patients' actual opioid use after hospital discharge. Individualized point of care tools are needed to determine an appropriate opioid prescription size.